2003
DOI: 10.1073/pnas.0737048100
|View full text |Cite
|
Sign up to set email alerts
|

IL-15Rα expression on CD8+T cells is dispensable for T cell memory

Abstract: The generation and maintenance of immunological memory requires the activation, expansion, and persistent proliferation of antigen-specific T cells. Recent work suggests that IL-15 may be important for this process. Surprisingly, we now find that expression of the high-affinity receptor for IL-15, IL-15R␣, on T cells is dispensable for the generation or maintenance of memory CD8 ؉ T cells. By contrast, IL-15R␣ expression on cells other than T cells is absolutely critical for this function. These findings may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
157
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 28 publications
5
157
1
1
Order By: Relevance
“…IL-15 is important in maturation of dendritic cells (DCs) for Ag presentation (36), suggesting that generation of effector CD8 ϩ T cells may be impaired at the expansion phase after BCG infection, resulting in a decrease in the number of Ag-specific CD8 ϩ T cells in the lung at the late stage of infection. Recent studies have demonstrated that primary responses to LCMV and OVA were readily generated in IL-15 Ϫ/Ϫ mice or IL-15R␣ Ϫ/Ϫ mice to a level equal to that in control mice (24,37). We have also reported that generation of Ag-specific CD8 ϩ T cells in IL-15 Tg mice and IL-15 Ϫ/Ϫ mice normally occurred after primary infection with L. monocytogenes (38,39).…”
Section: Discussionmentioning
confidence: 69%
“…IL-15 is important in maturation of dendritic cells (DCs) for Ag presentation (36), suggesting that generation of effector CD8 ϩ T cells may be impaired at the expansion phase after BCG infection, resulting in a decrease in the number of Ag-specific CD8 ϩ T cells in the lung at the late stage of infection. Recent studies have demonstrated that primary responses to LCMV and OVA were readily generated in IL-15 Ϫ/Ϫ mice or IL-15R␣ Ϫ/Ϫ mice to a level equal to that in control mice (24,37). We have also reported that generation of Ag-specific CD8 ϩ T cells in IL-15 Tg mice and IL-15 Ϫ/Ϫ mice normally occurred after primary infection with L. monocytogenes (38,39).…”
Section: Discussionmentioning
confidence: 69%
“…Whereas IL-7 promotes the survival of both naive and memory CD8 + T cells, IL-15 uniquely supports basal memory CD8 + T cell proliferation [20,41,48]. Thus, in the absence of proliferative IL-15 signals, effector/memory CD8 + T cells undergo slow atrophy in number until they become essentially undetectable under certain conditions [20,49]. After infection with Mtb, we now show that the accumulation of CD8 + T cells in the lungs of IL-15 -/-mice was indeed substantially reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that IL-15R␣ not only acts as a component of IL-15R complex for the high affinity binding, but can also act to present IL-15 to adjacent cells in vitro and in vivo (40,41,65,67,72). In the GC reaction, effective delivery of survival and proliferative signals only to appropriate clones having higher affinity BCR is essential so as not to expand overwhelming numbers of clones with low affinity BCR.…”
Section: Discussionmentioning
confidence: 99%